The fund agreement in the courts: volume II : further jurisprudence involving the articles of agreement of the International Monetary Fund - Gold, Joseph (Washington, D.C. : International Monetary Fund, 1962)
This volume, like others takes a close look at the new cases through the telescope of the Fund's Articles and practice. It's a collection of 24 studies related principally to litigation involving the Fund's Articles of Agreement.
Volume 3- Further studies in jurisprudence involving the articles of agreement of the International Monetary Fund.
Includes bibliographical references and index.
rua 21/06/2017
Loans
Keywords: International Monetary Fund